2017
DOI: 10.3174/ajnr.a5177
|View full text |Cite
|
Sign up to set email alerts
|

Solid Lymph Nodes as an Imaging Biomarker for Risk Stratification in Human Papillomavirus–Related Oropharyngeal Squamous Cell Carcinoma

Abstract: BACKGROUND AND PURPOSE:Human papillomavirus-related oropharyngeal squamous cell carcinoma is associated with cystic lymph nodes on CT and has a favorable prognosis. A subset of patients with aggressive disease experience treatment failure. Our aim was to determine whether the extent of cystic lymph node burden on staging CT can serve as an imaging biomarker to predict treatment failure in human papillomavirus-related oropharyngeal squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Very few studies have investigated the associations between radiologic ENE on CT and survival outcomes in patients with HPV-related OPSCC. Rath et al (14) demonstrated that radiologic ENE was an independent worse predictor of disease-free survival in patients with HPV-related OPSCC (hazard ratio = 3.3, p = 0.001). In contrast, Liu et al (15) showed that radiologic ENE was not a significant prognosticator of PFS in patients with HPV-related OPSCC, although they did find a trend towards worse PFS with radiologic ENE ( p = 0.098), as in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies have investigated the associations between radiologic ENE on CT and survival outcomes in patients with HPV-related OPSCC. Rath et al (14) demonstrated that radiologic ENE was an independent worse predictor of disease-free survival in patients with HPV-related OPSCC (hazard ratio = 3.3, p = 0.001). In contrast, Liu et al (15) showed that radiologic ENE was not a significant prognosticator of PFS in patients with HPV-related OPSCC, although they did find a trend towards worse PFS with radiologic ENE ( p = 0.098), as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a subset of patients with atypical features of HPV-related OPSCC, including radiologic ENE or matted lymph nodes, the cancer tends to show aggressive behavior, including local recurrence with distant metastases (111213). Recently, two studies that used CT to investigate the associations between radiologic ENE and survival outcomes in patients with HPV-related OPSCC yielded conflicting results: one showed that radiologic ENE had significant prognostic value (14), while the other found that it had no value (15). One previous study showed that contrast-enhanced magnetic resonance (MR) can be useful for lymph node characterization in head and neck squamous cell carcinoma (16).…”
Section: Introductionmentioning
confidence: 99%
“…Fine needle aspiration cytology (FNAC) with ultrasonography, computed tomography (CT), and MRI are the techniques generally used for the local staging of OPSCC, while positron emission tomography (PET)-CT is useful in locally advanced stages and for carcinomas of unknown primary origin [7][8][9][10][11]. Several studies [11][12][13][14] have reported differences in imaging features of OPSCC by HPV status. HPV-related lymph nodes (LNs) often tend to present with large cystic masses, with a clinically and radiologically smaller or even occult primary tumor (PT) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Cystic lesions were defined as those that included more than 30% of the low-density area. Because previous studies used a cut-off value of 20% [3], we used a cut-off value of 30% in the present study to make the definition as cyst lesions more consistent. The design of this study was approved by our Institutional Review Board and Ethics Committee (approval number: 31-083 [9582]).…”
Section: Methodsmentioning
confidence: 99%